Global heat stress on health, wildfires, and agricultural crops under different levels of climate warming. (July 2019) - Sun, Qiaohong; Miao, Chiyuan; Hanel, Martin; Borthwick, Alistair G.L.; Duan, Qingyun; Ji, Duoying; Li, Hu
Abstract: The effects of heat stress are spatially heterogeneous owing to local variations in climate response, population density, and social conditions. Using global climate and impact models from the Inter-Sectoral Impact Model Intercomparison Project, our analysis shows that the frequency and intensity of heat events increase, especially in tropical regions (geographic perspective) and developing countries (national perspective), even with global warming held to the 1.5 °C target. An additional 0.5 °C increase to the 2 °C warming target leads to >15% of global land area becoming exposed to levels of heat stress that affect human health; almost all countries in Europe will be subject to increased fire danger, with the duration of the fire season lasting 3.3 days longer; 106 countries are projected to experience an increase in the wheat production-damage index. Globally, about 38%, 50%, 46%, 36%, and 48% of the increases in exposure to health threats, wildfire, crop heat stress for soybeans, wheat, and maize could be avoided by constraining global warming to 1.5 °C rather than 2 °C. With high emissions, these impacts will continue to intensify over time, extending to almost all countries by the end of the 21st century: >95% of countries will face exposure to health-related heat stress, with India and Brazil ranked highest for integrated heat-stress exposure. The magnitude of the changes in fire season length and wildfire frequency are projected to increase substantially over 74% global land, with particularly strong effects in the United States, Canada, Brazil, China, Australia, and Russia. Our study should help facilitate climate policies that account for international variations in the heat-related threats posed by climate change. Highlights: We assessed the influences of 1.5 °C and 2.0 °C warmings on the multiple sectors. 0.5 °C less warming would help avoid 38% of the health-related heat exposure. 0.5 °C less warming would help avoid 50% of the exposure to wildfire. 0.5 °C less warming would help avoid 48% of the maize-related heat exposure. Developing countries are likely to experience greater exposure to heat extremes.